UPAYA MENINGKATKAN KETERAMPILAN BERPIKIR KRITIS SISWA MELALUI MODEL PROBLEM BASED LEARNING PADA PEMBELAJARAN IPA KELAS IV SDN KENARI 07 - Ranita Fitri; Tunjungsari Sekaringtyas; Julius Sagita (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to improve students' critical thinking skills through the Problem Based Learning model in science learning for grade IV of SDN Kenari 07 Central Jakarta with 32 students. The method used is Classroom Action Research (CAR) with collection techniques by observation using teacher and student action monitoring sheets, evaluation sheets, and documentation. The results of the study indicate that the Problem Based Learning model can improve students' critical thinking skills that have been carried out on the science subject content in grade IV of SDN Kenari 07 Central Jakarta, the results shown in cycle I students' critical thinking skills got a percentage of 22% and in cycle II 84% so that the increase that occurred was 62% and based on the results of the research for each cycle, it can be concluded that science learning using the Problem Based Learning model can improve students' critical thinking in grade IV-A of SDN Kenari 07 Central Jakarta.